Identification and evaluation of antiviral activity of novel compounds targeting SARS-CoV-2 virus by enzymatic and antiviral assays, and computational analysis - Ivana Nemčovičová; Katarína Lopušná; Iveta Štibrániová; Fabio Benedetti; Federico Berti; Fulvia Felluga; Sara Drioli; Mattia Vidali; Jaroslav Katrlík; Lucia Pažitná; Alena Holazová; Jana Blahutová; et al. (Taylor & Francis Group, 2024)
AbstractThe viral genome of the SARS-CoV-2 coronavirus, the aetiologic agent of COVID-19, encodes structural, non-structural, and accessory proteins. Most of these components undergo rapid genetic variations, though to a lesser extent the essential viral proteases. Consequently, the protease and/or deubiquitinase activities of the cysteine proteases Mpro and PLpro became attractive targets for the design of antiviral agents. Here, we develop and evaluate new bis(benzylidene)cyclohexanones (BBC) and identify potential antiviral compounds. Three compounds were found to be effective in reducing the SARS-CoV-2 load, with EC50 values in the low micromolar concentration range. However, these compounds also exhibited inhibitory activity IC50 against PLpro at approximately 10-fold higher micromolar concentrations. Although originally developed as PLpro inhibitors, the comparison between IC50 and EC50 of BBC indicates that the mechanism of their in vitro antiviral activity is probably not directly related to inhibition of viral cysteine proteases. In conclusion, our study has identified new potential noncytotoxic antiviral compounds suitable for in vivo testing and further improvement.